DUAL-FREQUENCY CONFORMAL SERIES FEED ANTENNA FOR TELEMETRY APPLICATIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
In this study, a conformal series-feed array antenna for telemetry applications is proposed, operating at 900 MHz and 2.4 GHz. The dual-frequency antenna features a simple geometric design consisting of 5-element and 10-element series-fed arrays, respectively, within a single ground plane, and is fabricated using Roger 5880 material. The proposed antenna was mounted on the cylinder tube, and various performance parameters were analyzed. The antenna demonstrates reliable dual-band operation, with maximum gains of 7.04 dBi at 930 MHz and 5.85 dBi at 2.46 GHz, along with favorable bandwidth and radiation characteristics. These results highlight the antenna’s potential as a compact and effective solution for conformal telemetry systems.
Keywords: Series feed network; Conformal antenna; Array; Telemetry